CHARACTERIZATION OF THREE BENZOATE DEGRADING ANOXYGENIC PHOTOSYNTHETIC BACTERIA ISOLATED FROM THE ENVIRONMENT - SURYANTO, DWI; SUWANTO, ANTONIUS; MERYANDINI, ANJA (BIOTROPIA, 2011)
Three anoxygenic photosynthetic bacteria, DS-1, DS-4 and Cas-13, have been examinated for the morphological and physiological properties. All strains were rod-shape cells with a swollen terminal end Gram negative, motile, non-halophilic, non-alkalophilic and non-acidophilic, and capable of utilizin benzoate aerobically and photo-anaerobically. Sequence analysis of part of 16S rRNA genes showed that DS 1 and Cas-13 were closely related to Rhodopseudomonas palustris Strain 7 with a similarity of 97%, wherea DS-4 may not be closely related to the former two strains with a similarity of 78% based on the constructe phylogenic tree. Spectral analysis indicated that the three bacteria had bacteriochlorophyl a and norma spirilloxanthin series. Growth in medium enriched with vitamin and supplemented with benzoate as their sole C-sources wa better than in medium without vitamin. Benzoate degradation in medium with vitamin was accelerated. Th ability to grow on benzoate without added vitamins indicated that the bacteria were able to synthesize the own vitamins. Key words: anoxygenic photosynthetic bacteria/ benzoate degradation/ 16S rRNA gene.